Innovation through individual-focused transformational leadership in China: mediation by leader identification and cross-level moderation by team-focused leadership and innovation climate - Wang, Xiaokang; Park, Heetae; Kim, Hee Jin (Frontiers in Psychology, 2025)
In the new phase of economic transformation and social development, innovation has emerged as a critical issue. Corporate innovation largely depends on the innovative behavior of its members, making it crucial to understand the impact of transformational leadership on employees’ innovative behavior. We conducted a study from the perspective of relational identity theory. Questionnaire data were collected from April to June 2024 through a professional survey company in China that recruited 640 members and leaders of 160 teams. The analysis results are as follows: First, individual-focused transformational leadership was found to have a positive effect on individual innovative behavior. Second, leader identification played a significant mediating role in the relationship between individual-focused transformational leadership and individual innovative behavior. Third, team-focused transformational leadership exhibited a significant negative cross-level moderating effect on the relationship between individual-focused transformational leadership and leader identification. Lastly, team innovative climate showed a significant positive cross-level moderating effect on the relationship between leader identification and individual innovative behavior.